EXPLORING DESIGN STUDENTS' INTERPRETATION OF CHINESE CULTURAL INFLUENCES IN PRODUCT DESIGN - Chu , Xiao Xing; Abdul Latef , Azlin Sharina; Kuan , Tenh Hock; Hapiz , Hana (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In a globalized context, this study explores how design students integrate Chinese cultural elements into modern product design. Despite China's rich cultural heritage offering ample inspiration, there's a gap in authentically applying these elements globally. Through qualitative methods like interviews and observation, it examines 20 students' cognitive logic and strategies in cultural symbol selection, model application, and user experience adaptation. Findings show students rely on existing cultural schemas but struggle with adjusting models dynamically and balancing cultural connotations with modern design. The study innovatively constructs a "cultural schema-semiotics-user experience" framework, integrating COD theory, Peirce's semiotics, and Hofstede's cultural dimensions. It reveals the need to balance signifier substitution, signified extension, and contextual adaptation, offering a path for cultural integration in design education to enhance students' cultural sensitivity and innovation.